Virgibacillus senegalensis sp. nov., a new moderately halophilic bacterium isolated from human gut. (November 2015) - Seck, E.; Rathored, J.; Khelaifia, S.; Croce, O.; Robert, C.; Couderc, C.; Di Pinto, F.; Sokhna, C.; Raoult, D.; Lagier, J.-C.
Abstract: Virgibacillus senegalensis SK-1 T (= CSUR P1101 = DSM 28585) is the type strain of V. senegalensis sp. nov. It is an aerobic, Gram positive, moderately halophilic, motile bipolar flagellum isolated from a healthy Senegalese man. Here we describe the genomic and phenotypic characteristics of this isolate. The 3 755 098 bp long genome (one chromosome, no plasmid) exhibits a G + C content of 42.9% and contains 3738 protein-coding and 95 RNA genes.